PELATIHAN SAT (SELF REGULATION, ASSERTIVENESS, TIME MANAGEMENT) DAN PROKRASTINASI AKADEMIK PADA SISWA SMA - Florentina Yuni Apsari, Ermida, (EXPERIENTIA : Jurnal Psikologi Indonesia, 2012)
High school students tend to do academic procrastination, which is behaviour that relates to delay action towards academic tasks during their study. Refer to this condition, SAT training (Self Regulation, Assertiveness and Time Management) is designed to reduce academic procrastination of high school students. Subjects are high school students in class XI. This research uses experimental design one-group pretest-posttest design. The results showed t values = 1, 403 with p = 0.175 (p